Carcinoembryonic antigen as a tumor marker in lung cancer – is it clinically useful? - Okuła, Agnieszka; Karczmarek-Borowska, Bożenna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
Introduction. Lung cancer is the most common cancer in the Western world. Annually there are approximately 1.8 million new cases worldwide. It is characterized by poor prognosis with a 5-year survival of 10-17% depending on the country. Contributing to this poor prognosis is a mainly late diagnosis, as well as a fairly frequent recurrence despite radical surgery. Over the years, scientists have been searching for a tumor marker that would be useful for patients with lung cancer. Aim. The aim of this study is to discuss the significance of carcinoembryonic antigen (CEA) in the diagnosis, prognosis of the disease course, and monitoring patients with lung cancer. Methods. Review of the literature using the PubMed database, Termedia, Via Medica and the key issue: carcinoembryonic antigen as a tumor marker in lung cancer. Conclusions. Serum CEA level can be a reliable complement to the diagnosis of lung cancer. It can be helpful in preoperative prediction of disease course and qualification for adjuvant treatment of non-small cell lung cancer especially adenocarcinoma. Trends and normalization of CEA during chemotherapy have an impact on progression-free survival and overall survival (OS) of patients. Various available publications describe CEA as a marker for metastatic lung cancer, which is the most specific for metastasis in the liver and brain.
Keywords: carcinoembryonic antigen; lung cancer; prognostic factor; tumor marker